2003
DOI: 10.1038/sj.bmt.1703846
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism analysis following allogeneic peripheral blood stem cell transplantation with reduced-intensity conditioning

Abstract: Summary:We have performed a prospective study to evaluate early chimerism and its kinetics after allogeneic peripheral blood stem cell transplantation among 68 patients who received a reduced-intensity conditioning (RIC) regimen with fludarabine plus melphalan (n ¼ 40) or busulphan (n ¼ 28). Chimerism was analyzed by polymerase chain reaction amplification of short tandem repeats in unfractionated (UF) and/or fractionated nucleated cells from bone marrow and peripheral blood (PB). All of the patients showed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 18 publications
4
59
4
Order By: Relevance
“…4 Not surprisingly, we experienced more patients with MC after conditioning with RIC than with myeloablative conditioning, which has been described by others. [21][22][23] More importantly, however, high MC was no different using RIC than with myeloablative conditioning. High MC was correlated with graft failure and it is therefore undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…4 Not surprisingly, we experienced more patients with MC after conditioning with RIC than with myeloablative conditioning, which has been described by others. [21][22][23] More importantly, however, high MC was no different using RIC than with myeloablative conditioning. High MC was correlated with graft failure and it is therefore undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as the type of hematologic malignancy, amount of pretransplant therapy, source of hematopoietic stem cells, composition of the hematopoietic graft and whether patients received a related vs unrelated donor have been correlated with the development of CDC after RIC allogeneic HSCT. [27][28][29] We have also previously reported that killer immunoglobulin-like receptor/ligand matching may influence the achievement of T-cell CDC and the development of graft rejection after RIC allogeneic HSCT. 8 Strategies to enhance achievement of T-cell CDC may include increasing pretransplant conditioning intensity further and the use of prophylactic donor lymphocyte infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Valcarcel et al 40 studied 68 patients transplanted after conditioning with fludarabine (30 mg/m 2 on days À8 to À4) and melphalan (70 mg/ m 2 on days À3 and À2) in patients with lymphoid malignancies or fludarabine (30 mg/m 2 on days À9 to À5) and busulfan (total 10 mg/kg) in patients with myeloid malignancies. GVHD prophylaxis consisted of CSP and a short course of methotrexate (MTX).…”
Section: Variables Affecting Host-versus-graft Reactions Previous Chementioning
confidence: 99%